Structural and shielding properties of NiO/xCo3O4 nanocomposites synthesized by microwave irradiation method - Ali, Atif Mossad; Issa, Shams A. M.; Zakaly, Hesham M. H.; Pyshkina, Mariia; Somaily, H. H.; Algarni, H.; Rashad, M.; Saif, M.; H. A. A., Sidek; Matori, K. A.; M. Zaid, M. H. (Elsevier, 2020)
In the present study, nanocomposites with different ratios of NiO and Co3O4 (x = 0.3, 0.5, and 0.7) have been prepared via microwave oven and characterized using XRD. FLUKA code has been used to estimate the values of the mass attenuation coefficient (μm) for all samples. From the measurement, we found that when the thickness of the samples increases, the gamma transmission values decrease. Besides, the μm values increase as the Co3O4 content increase from 0.3 to 0.7%. At selected photon energy, the HVL, TVL, and MFP values decrease with increasing Co3O4 concentrations. At low energies (0.1–0.5 MeV), the linear decreasing trend in MAC values indication that photoelectric effect (PEA) (∝1/E3.5) dominance over this region. Afterward, at medium energy regions (0.5–1.33 MeV), the decrements in MAC values are insignificant as the Compton scattering (CS) (∝1/E) phenomenon dominates. As a conclusion, CoNi3 has superior effectiveness as a shielding material.